In-situ simultaneous surface finishing using abrasive flow machining via novel fixture. (February 2020) - Baraiya, Rajendra; Babbar, Atul; Jain, Vivek; Gupta, Dheeraj
Highlights: A novel fixture for simultaneous finishing of all surfaces of ring-shaped alloy workpiece is developed. Different machining parameters have been studied in terms of surface roughness on inner, outer, and side surface. Mechanism of finishing has been explained along with statistical analysis at 95 % confidence level. Metallurgical examination has been performed to reveal the surface endowment. Abstract: The present research investigations are based on the simultaneous finishing of ring-shaped cylindrical aluminium alloy workpiece having utility in multitude areas such as medical, defence, automobile, aerospace, and manufacturing ventures. To accomplish this objective, a novel in-situ fixture is designed and fabricated for simultaneous finishing of the inner, outer, and side surface. The silicone polymer-based abrasive media is prepared and is tested on the workpiece. The effect of different machining parameters is investigated in terms of response characteristics such as a change in surface roughness and percentage improvement. The surface roughness before and after abrasive flow machining has been analyzed under a microscope to reveal surface endowment. It has been pragmatically observed that abrasive mesh size, the concentration of abrasives, and a number of passes has a significant effect on change in surface roughness. The maximum percentage improvement in the surface roughness found to be 35.71 %, 37.89 %. and 27.16 % on the inner, outer, and side surface respectively. The surface micrographs after finishing showed the direction of abrasives, media flow direction, the direction of single point cutting tool, and material removal via ploughing effect owing to the high indentation of abrasive grits.